The Correlation of Library Personnel Motivation Work Attitude and Work Motivation to Job Performance in Nigeria - Qudus Ajibola Bankole; Mohammed Lawal Akanbi; Kabiru Gambari Sulaiman (Insaniyat : Journal of Islam and Humanities, 2023)
The purpose of this study was to reconnoiter the effects of library personnel work attitude and motivation as correlates of job performance in a survey of public libraries in Kwara state, Nigeria. This study employed a descriptive survey method of correlational type. This study applied an enumeration survey technique or total census to all library personnel in a nominated public library in Kwara State of Nigeria. This study employs three objectives to guide the study. Findings showed that library personnel had a good attitude about their jobs, and library personnel work motivation showed that employees in the library are provided with good working materials, and their workplace's management provides library personnel with opportunities for training and development. Also, the study on the job performance of library personnel found that library personnel set reasonable priorities for task completion, and personnel is always on time for deadlines and completion of tasks. Conclusively, years of experience at a job correlate significantly with job performance, whereas work attitudes and motivation do not correlate significantly. Based on the results, this study suggests a good relationship between library management and personnel to ensure a positive working attitude. Also, the library personnel should be able to establish a good working relationship to reduce the possibility of turnover.